Istanbul Grand Bazaar Evacuation System Vulnerability Assessment - Yucel, Gul; Arun, Gorun (TRANS TECH PUBLICATIONS LTD, 2010)
The Grand Bazaar is a historical trade centre more than 500 years in the historical peninsula of Istanbul, Turkey. It consists of almost 3,600 small shops from different sectors (such as jewellery, carpet, leather, souvenir, finance, restaurant, cafe, confection etc.), two Bedesten, 64 street and 16 Han (inn) buildings. The Bazaar has 21 main gates that open to different streets and have different relation with outside. More than 25000 staff work in the shops and 300-500 thousand users come to Bazaar daily depending on the season and day. The pedestrian density is changeable, depending on the place of the inner street and the type of the sector. The historical disaster records (earthquake, dated 1766 and 1894, the grand bazaar fire, dated 1954) show that there was evacuation vulnerability. The main gates (exit doors) and exit route need some rehabilitation for safety evacuation during any disaster. The aim of this study is to evaluate the Grand Bazaar's emergency evacuation vulnerability. The evacuation vulnerability factors question the width, length and natural illumination of the evacuation route, maintenance of the roof, presence of hazardous materials, door specifications as size, material, opening direction, maintenance and difference in elevation on the route and exit area such as staircase and thresholds.
Keywords: Disaster; vulnerability; evacuation; the Grand Bazaar; Construction & Building Technology; Engineering; Materials Science